Tellurium isotope cosmochemistry: Implications for volatile fractionation in chondrite parent bodies and origin of the late veneer. (15th September 2021) - Hellmann, Jan L.; Hopp, Timo; Burkhardt, Christoph; Becker, Harry; Fischer-Gödde, Mario; Kleine, Thorsten
Abstract: Tellurium stable isotope compositions and abundances (δ 128/126 Te relative to SRM 3156) are reported for 43 ordinary, enstatite, and Rumuruti chondrites, which together with results from a companion study on carbonaceous chondrites are used to assess the origin of volatile element fractionations in chondrites. Whereas Te isotope variations among carbonaceous chondrites predominantly reflect mixing between isotopically light chondrules/chondrule precursors and CI-like matrix, Te isotope variations among non-carbonaceous chondrites mainly result from Te redistribution during parent body thermal metamorphism. The enstatite chondrites in particular display increasingly heavy Te isotopic compositions and decreasing Te concentrations with increasing degree of metamorphism, indicating migration of isotopically light Te from the strongly metamorphosed inner parts towards the cooler outer regions of the parent bodies. By contrast, ordinary and Rumuruti chondrites display less systematic Te isotope variations, implying more localized redistribution of Te during parent body thermal metamorphism. We also report Te stable isotope data for 19 terrestrial mantle-derived rocks. Peridotites with Al2 O3 contents close to those inferred for the bulk silicate Earth (BSE) exhibit uniform δ 128/126 Te values, which we interpret to represent the Te isotopic composition of the BSE. This composition overlaps with the Te isotope composition of some volatile-rich carbonaceous chondrites (most notably CM chondrites), but also with that of enstatite chondrites. Comparison of the Te results to Se isotopes and Se/Te ratios shows that due to uncertainties in the composition of the BSE and the isotopic composition of bulk chondrite parent bodies, neither Te isotopes alone nor the combined Se-Te elemental and isotopic systematics can distinguish between a carbonaceous and enstatite chondrite-like late veneer, which is the presumed source of Se and Te in the BSE. Together, the results of this study illustrate that the relative abundances and mass-dependent isotope compositions of volatile elements like Se and Te are modified by physical and chemical processes occurring after planetary accretion, which severely complicates their use as genetic tracers. A corollary of this is that contrary to prior proposals the Se-Te systematics are not contradicting an inner solar system origin of the late veneer, as it has been inferred using nucleosynthetic isotope anomalies of other elements.